A fiber-delivered, multi-line nanosecond source for single-shot spectro-polarimetric scattering measurements - Livecchi, Thomas; Urban, Ben E. (Advanced Optical Technologies, 2025)
We here describe a nanosecond, multi-line laser source that preserves partial linear polarization after transmission through a 100-m large-core graded-index (GRIN) fiber. The system generates narrow emission lines between 473 and 600 nm, evenly spaced by the silica Raman shift of ∼440 cm-1, from a Q-switched nanosecond pump coupled into the fiber. Despite multimode propagation, the cascaded beams emerge close to diffraction-limited Gaussian profiles due to nonlinear mode self-cleaning, while the residual pump remains multimodal. Across the emission lines, the degree of linear polarization (DoLP) ranges from 0.1 to 0.6 depending on the wavelength. As an application, we demonstrate single-shot, multiwavelength spectro-polarimetric reflectance, simultaneously measuring DoLP at all cascaded lines. To our knowledge, this is the first demonstration of wavelength-dependent polarization retention through a 100-m large-core GRIN fiber.